Performance of special engineering and geological researches in the territories of industrial and urban agglomerations - Соколов, Віктор; Удалов, Ігор; Кононенко, Аліна (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2021)
Formulation of the problem. The article is devoted to the description of the implementation of special engineering-geological researches in the territories of industrial and urban agglomerations.The purpose of the article is to show the possibilities of special geophysical researches while studying hazardous geological processes and the determination of the physical and mechanical properties of soils under the foundations of buildings in conditions of dense urban development.Materials and methods. To achieve the main goal, special equipment was used in the work – a horizontal sounding and logging unit. It is intended for mass and most reliable research of soil properties at the base of existing buildings and structures. Using this installation, the following tasks are solved:drilling horizontal wells;selection of soil monoliths;static sounding using «Pika» equipment;radioactive logging;pressiometric researches of soils;immersion of injectors to consolidate the soil.Results. Analysis of the performed engineering and geological surveys at the site of the emergency workshop № 22 of PA «Krasitel» in the city of Rubezhnoye, Lugansk region and at the site of reconstruction of the hostel on the street Studencheskaya, 4 in Kharkov showed the possibility of using special geophysical research in the conditions of industrial and urban agglomerations.To find out the cause of the emergency deformation of the structure of the emergency workshop № 22 of PA «Krasitel», a study of soils was carried out using the method of radioactive logging. Obtained results are presented in the form of a diagram of the isodensity of the base soils. Zone of decompaction of the base soils has been identified and delineated. Based on the materials obtained, it was concluded that the main reason for the collapse of a part of the building is the additional subsidence of the foundations as a result of mechanical removal of soils into the destroyed sewer collector located below the base of the foundations.On the site of reconstruction of the hostel on the street Studencheskaya, 4 in Kharkov, the density of soils under the foundations of the existing building was determined by the method of gamma-gamma logging. It was found that under the foundations in the zone of stress development, an increase in the density of the foundation soils is recorded. Outside the stressed zone (between foundations), the density of soils is significantly reduced and corresponds to the background values.Scientific novelty and practical significance. Scientific novelty – the choice of a complex of special geophysical studies in researches of hazardous geological processes and to determine the physical and mechanical properties of soils under the foundations of buildings in conditions of dense urban development of industrial and urban agglomerations is scientifically substantiated.Practical application of the proposed results – the validity of the use of geophysical methods in the practice of exploration work on a par with the traditionally used equipment has been confirmed.